A cross sectional study to assess knowledge, attitude and practice of rational antibiotic prescription among resident doctors - Antony, Anatte; Mohamedali, Seema P.; M., Anuradha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Irrational prescription is a major contributor to the antimicrobial resistance. Resident doctors are the major focus of interventional programs aimed at rational prescription of antibiotics. So, their knowledge, attitude and practice regarding rational antibiotic prescription need to be assessed to plan future strategies. Methods: A questionnaire based cross sectional study among interns and resident doctors of a Government Medical College was conducted. Questionnaire consisted of questions to assess knowledge, attitude and practice of resident doctors in rational antibiotic prescriptions and multiple-choice questions to assess practice of hospital antibiotic policy. Results: 80 participants were enrolled in the study. All participants responded to yes or no questions and 47 answered multiple choice questions. 40% were aware of the current hospital antibiotic policy and 29% knew the term antibiotic stewardship. Only 15% were confident in their knowledge on antimicrobial resistance. 87.5% think there is no use in prescribing an antibiotic in common cold. 36.3% overprescribes antibiotics in their daily practice. Only 32.5% practiced de-escalation. 90% were educating patients regarding correct use of antibiotics. 90% send samples for culture and sensitivity but only 22.2% waited for results to start antibiotics. Conclusions: There is a need for approaches that includes implementation of antibiotic policy and to plan for effective teaching programs regarding antibiotic resistance and importance of rational prescription of antibiotics which can improve the quality of antibiotic prescription and minimize antibiotic resistance.